Finance and Development, September 2006. (Finance and Development; Finance and Development ;, 2006)
The Economics of Demographics provides a detailed look at how the biggest demographic upheaval in history is affecting global development. The issue explores demographic change and the effects of population aging from a variety of angles, including pensions, health care, financial markets, and migration, and looks specifically at the impact in Europe and Asia. Picture This looks at global demographic trends, while Back to Basics explains the concept of the demographic dividend. Country Focus spotlights Kazakhstan, while People in Economics profiles Nobel prize winner Robert Mundell. IMF Economic Counsellor Raghuram Rajan argues for further change in India's style of government in his column, Straight Talk.